Pengaruh disiplin kerja dan motivasi kerja terhadap kinerja karyawan pada PT. Perkasa Beton Batam - Situmorang, Betharia Claudina; Siagian, Mauli (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Useful research would like to know partially and simultaneously the effect of work discipline and work motivation on the performance of employees of PT Perkasa Beton Batam. The population of the following survey is a total of 112 employees in all departments. The total number of samples collected for the survey was 112 respondents. In this test, the saturated sampling method is used, which is used for the sampling method. The use of the questionnaire is the data collection method. The data was processed using SPSS version 26.0. The survey method used is a quantitative method. The test results show that work discipline has a positive and significant effect on the performance of PT Perkasa Beton Batam employees, the t count is 10,113 > t table 1.981967, and work motivation has a positive effect on the performance of PT Perkasa Beton Batam employees. have a significant effect. the acquisition of t count is 3.679 > t table 1.981967. The results of this test also show that work discipline and work motivation simultaneously affect the performance of PT Perkasa Beton Batam employees. The value is f count 498.847 > f Table 3.08.